Gone West - Cooke, Alistair, 1908-; British Broadcasting Corporation. Television Service; Time-Life Films (New York : Time-Life Multimedia, 1972)
Deals with the Louisiana Purchase, the Lewis and Clarke Expedition, the exploration of the distant reaches of the waterways, the forcing of Indian nations west of the Mississippi, and the gold rush.
Title from data sheet.
U standard.
Producer, Michael Gill; writer and narrator, Alistair Cooke.
Keywords: West (U.S.) -- History